Heparin Oligosaccharides Have Antiarrhythmic Effect by Accelerating the Sodium-Calcium Exchanger - Godoy, Carlos M. G. de; Vasques, Ênio R.; Caricati-Neto, Afonso; Tavares, José G. P.; Alves, Beatriz J.; Duarte, Juliana; Miranda-Ferreira, Regiane; Lima, Marcelo A.; Nader, Helena B.; Tersariol, Ivarne L. dos Santos (Frontiers in Cardiovascular Medicine, 2018)
Background: Blockage of the Na+/Ca2+ exchanger (NCX) is used to determine the role of NCX in arrhythmogenesis. Trisulfated heparin disaccharide (TD) and Low Molecular Weight Heparins (LMWHs) can directly interact with the NCX and accelerate its activity. Objective: In this work, we investigated the antiarrhythmic effect of heparin oligosaccharides related to the NCX activity. Methods: The effects of heparin oligosaccharides were tested on the NCX current (patch clamping) and intracellular calcium transient in rat cardiomyocytes. The effects of heparin oligosaccharides were further investigated in arrhythmia induced in isolated rat atria and rats in vivo. Results: The intracellular Ca2+ concentration decreases upon treatment with either enoxaparin or ardeparin. These drugs abolished arrhythmia induction in isolated atria. The NCX antagonist KB-R7943 abolished the enoxaparin or ardeparin antiarrhythmic effects in isolated atria. In the in vivo measurements, injection of TD 15 min both before coronary occlusion or immediately after reperfusion, significantly prevented the occurrence of reperfusion-induced arrhythmias (ventricular arrhythmia and total AV block) and reduced the lethality rate. The patch clamping experiments showed that, mechanistically, TD increases the forward mode NCX current. Conclusion: Together, the data shows that heparin oligosaccharides may constitute a new class of antiarrhythmic drug that acts by accelerating the forward mode NCX under calcium overload.